2019
DOI: 10.1108/ijppm-02-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between TQM and SMEs’ performance

Abstract: Purpose The purpose of this paper is to empirically test the association between total quality management (TQM) and small and medium enterprises’ (SMEs) performance. In particular, it examines whether organizational culture (OC) has a mediating effect on the TQM–SME performance relationship. Design/methodology/approach The conceptual model for this study was developed based on the literature review of TQM, OC and SME performance. As the research framework, a self-administered questionnaire was used to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 111 publications
(194 reference statements)
6
38
0
6
Order By: Relevance
“…This technique is consistent with the previous studies that used EO, MO and TQM as a single construct (Aloulou, 2018;Amin et al, 2016;Calvo et al, 2014). With regard to SMEs' performance, one single construct rather than the multiple dimensions (financial and nonfinancial) was utilised in this study's analysis to reflect the total performance of the firm (Hilman et al, 2019;Jusoh, 2008). Therefore, this paper aims to examine the effect of EO, MO and TQM as one construct to improve the understanding on how they relate to other variables.…”
Section: Measurement Model Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…This technique is consistent with the previous studies that used EO, MO and TQM as a single construct (Aloulou, 2018;Amin et al, 2016;Calvo et al, 2014). With regard to SMEs' performance, one single construct rather than the multiple dimensions (financial and nonfinancial) was utilised in this study's analysis to reflect the total performance of the firm (Hilman et al, 2019;Jusoh, 2008). Therefore, this paper aims to examine the effect of EO, MO and TQM as one construct to improve the understanding on how they relate to other variables.…”
Section: Measurement Model Resultssupporting
confidence: 53%
“…Numerous studies have established the importance of TQM approach in hotel industries (Amin et al, 2016), manufacturing organisations (Bhatia and Awasthi, 2018;Patyal and Koilakuntla, 2017), SME firms (Sahoo and Yadav, 2017), public organizations (Al-Dhaafri et al, 2016) and service organisations (Yasin et al, 2004). Thus, TQM is considered a mechanism to improve firm performance and achieve competitive advantage (Hilman et al, 2019;Ferdousi et al, 2018;Calvo-Mora et al, 2014;Yunis et al, 2013). Organisations that implement TQM obtain a competitive advantage over firms that do not (Valmohammadi and Roshanzamir, 2015;Fening, 2012).…”
Section: Impact Of Eo Mo and Tqm On Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Hilman et al (2019) revealed that TQM practices significantly influence SMEs' performance in Riyadh, Mecca, and Eastern Saudi Arabia regions. The researchers also demonstrated that TQM practices could ensure a constant quality improvement in processes and employees' efforts to achieve the expected results.…”
Section: Discussion Of the Findingsmentioning
confidence: 93%